2013
DOI: 10.1021/la400835n
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Loading and Unloading Procedures for Gecko-Inspired Controllable Adhesives

Abstract: The importance of loading and unloading procedures has been shown in a variety of different methods for biological dry adhesives, such as the fibers on the feet of the Tokay gecko, but biomimetic dry adhesives have yet to be explored in a similar manner. To date, little work has systematically varied multiple parameters to discern the influence of the testing procedure, and the effect of the approach angle remains uncertain. In this study, a synthetic adhesive is moved in 13 individual approach and retraction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…This arose from the difference in contact area between the top, flat edge and curved edge faces of the pillar. In a separate study the authors demonstrated significant preload dependence on adhesion after shearing towards the curved face [71]. Similarly, Parness et al have shown that wedge-shaped pillars, with a wide base and narrow tip, exhibit negligible normal adhesion unless the pillars are pre-sheared to increase the contact area [55].…”
Section: Effects Of Fibre Geometry On Adhesionmentioning
confidence: 85%
“…This arose from the difference in contact area between the top, flat edge and curved edge faces of the pillar. In a separate study the authors demonstrated significant preload dependence on adhesion after shearing towards the curved face [71]. Similarly, Parness et al have shown that wedge-shaped pillars, with a wide base and narrow tip, exhibit negligible normal adhesion unless the pillars are pre-sheared to increase the contact area [55].…”
Section: Effects Of Fibre Geometry On Adhesionmentioning
confidence: 85%
“…39 Our work aims to address these topics while also exploring the grip-release mechanisms of our gecko-inspired adhesives in humid and wet environments. Geometrically anisotropic halfcylinder microfibers, 44,45 as well as tilted half-cylinder microfibers, 46 yield high adhesion and low adhesion states by controlling the loading path (approach−shear−retraction). Shear in one direction results in a large contact area and high friction and adhesion, referred to as the "grip state".…”
Section: Introductionmentioning
confidence: 99%
“…20 Detachment via peeling is also desirable because the adhesion force can be modulated by varying the peel angle. [21][22][23][24] Geckos 25 and tree frogs 3 have both been shown to splay their limbs to control their adhesion to surfaces where the peel angle is kept low to maintain contact and increased to pull out. In biomimetic systems, the effect of structured surfaces on peeling has been well-studied in dry [26][27][28] and wet 28,29 environments, but less so in completely ooded conditions.…”
Section: Introductionmentioning
confidence: 99%